Abordagens heurísticas para o problema de escalonamento de lotes em máquinas paralelas com penalidades por atraso - Medeiros, José Maurício Fernandes (2023)
This work addresses the identical parallel batch machines scheduling problem subject to tardiness penalties, release dates, and job families. In this environment, jobs of the same family are partitioned into batches and each batch is assigned to a machine. The jobs are processed simultaneously and are subject to the release date and processing time of the batch to which they belong. The objective is to determine the sequence of batches to be processed on each machine in order to minimize the total weighted tardiness. To solve the problem, two metaheuristic algorithms are proposed, employing local search procedures with multiple neighborhood structures and perturbations mechanisms. Computational experiments are conducted on known instances, and the results are analyzed and compared with those obtained using other methods found in the literature.